2015
DOI: 10.5483/bmbrep.2015.48.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid pore-channel hypothesis: effect of ethanol on aggregation state using frog oocytes for an Alzheimer's disease study

Abstract: Alzheimer's disease severely compromises cognitive function. One of the mechanisms to explain the pathology of Alzheimer’s disease has been the hypotheses of amyloid-pore/channel formation by complex Aβ-aggregates. Clinical studies suggested the moderate alcohol consumption can reduces probability developing neurodegenerative pathologies. A recent report explored the ability of ethanol to disrupt the generation of complex Aβ in vitro and reduce the toxicity in two cell lines. Molecular dynamics simulations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…While the pathogenic mechanism of human Parkinson's disease is still not fully understood, oxidative stress and cytotoxicity are thought to play an important role in the degeneration of dopaminergic neurons [63] , [64] , [69] , [70] , [71] , [72] , [73] , [74] . Mechanistically, it is known that dopamine neurotransmitter is chemically labile and its oxidation products, such as dopamine quinones and semiquinones, are highly cytotoxic to neurons in general and dopaminergic neurons in particular [63] , [64] , [69] .…”
Section: Basic and Clinical Evidence On The Beneficial Effects Of mentioning
confidence: 99%
“…While the pathogenic mechanism of human Parkinson's disease is still not fully understood, oxidative stress and cytotoxicity are thought to play an important role in the degeneration of dopaminergic neurons [63] , [64] , [69] , [70] , [71] , [72] , [73] , [74] . Mechanistically, it is known that dopamine neurotransmitter is chemically labile and its oxidation products, such as dopamine quinones and semiquinones, are highly cytotoxic to neurons in general and dopaminergic neurons in particular [63] , [64] , [69] .…”
Section: Basic and Clinical Evidence On The Beneficial Effects Of mentioning
confidence: 99%
“…Considering AD’s complex multifactorial etiology, phytochemicals that have antioxidant as well as AChE inhibitory activity have been considered to be safer and better therapeutic candidates for treating AD (Parodi et al. 2015 ). Antioxidant therapy has proven successful for improving cognitive function and behavioral deficits in patients with mild to moderate AD (Gutzmann and Hadler 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies by others and our group suggest that AβPs directly incorporate into the membrane and form channels (pores) that allow the passage of Ca 2+ and other cations, and that the resulting change in [Ca 2+ ] i may be a primary pathogenetic event in AβP neurotoxicity [110][111][112]. Neurotoxic peptide fragments of AβP, including AβP(1-40), AβP (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and AβP , have been demonstrated to incorporate into artificial planar lipid membranes and form giant multi-level pores (~5 nS) with cation (including Ca 2+ ) selectivity [113][114][115].…”
Section: Aβp-induced Ca Dyshomeostasismentioning
confidence: 99%
“…PrP C reportedly binds four Cu atoms in the octarepeat domain (-PHGGGWGQ-) in its N-terminal. Cu can also bind to His 96 and His 111 [69]. Huang et al found that PrP C binds to α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA)-type and/or NMDA-type glutamate receptors and affects their function in a Cu-dependent manner [70].…”
Section: Prion Diseases and Neurometalsmentioning
confidence: 99%